(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the Master of the Messengers, and upon all his family and companions. As for what follows: This research aims to clarify the jurisprudence rulings on issues related to the use of modern techniques in recitation during prayer. To achieve the goal of the research, it was extrapolated from what was mentioned in the legal texts and jurisprudence rules, and then the contemporary issues were extracted from them.The research showed the most important techniques that will be used for recitation during prayer, the advantages of these techniques and shed light on jurisprudential issues related to recitation devices during prayer, and the doctrinal issues that fall under them, and a statement of the jurisprudential adaptation for each issue. From this point of view, the idea of the topic came with (The rules for looking at the worshiper during his prayer in the books of jurists).